In or Out: Justice-Involved Women Characterization and Their Perceptions about Penal Sanctions - de Castro Rodrigues, Andreia (Women & criminal justice, 2025)
Women incarceration rates in Portugal are rising, nevertheless, noncustodial sanctions should be chosen, whenever possible. This paper aims to understand which women are being sentenced to noncustodial sanctions and which are not, and what they think about their penalty, considering that the penalties’ effectiveness is linked to how they are experienced. A self-report questionnaire was administered to 152 Portuguese women serving custodial and non-custodial sentences. Results demonstrated that women were not spared from prison, regardless of their parental and marital situation and whether or not this was their first penalty or if it was a nonviolent crime conviction. The women generally considered their sentences to be unfair, and rehabilitation was not considered the purpose guiding judges’ sentencing decisions. Implications for the rehabilitation of justice-involved women are discussed since these perceptions might compromise their adherence to the penalties and minimize its effectiveness.